LC-MS-BASED IDENTIFICATION OF BIOACTIVE COMPOUNDS FROM THE ETHANOLIC LEAF EXTRACT OF Pellacalyx fimbripetalus Korth - Nikho Prasetyo Pratama; Muhammad Fauzi; Nily Su’aida (AL ULUM: JURNAL SAINS DAN TEKNOLOGI, 2025)
The ethanolic leaf extract of Pellacalyx fimbripetalus (locally Tabuluh) was analyzed by Liquid Chromatography–Mass Spectrometry (LC-MS) to profile its bioactive constituents. Seventeen compounds were putatively identified, including tropane-type alkaloids, phenolic acids, flavonoids, glycosides, and fatty acids. Notably, orientin (a flavonoid C-glycoside) and chlorogenic acid derivatives were detected, which are known for antidiabetic and antioxidant activities. Several unusual compounds (e.g., a phenolic alkaloid and an iridoid-like glycoside) were present, potentially representing novel or understudied constituents. Traditional usage of P. fimbripetalus leaves in Bornean ethnomedicine for ailments such as cancer is supported by the discovery of diverse phytochemicals. This first LC-MS profiling of P. fimbripetalus leaf extract provides a basis for further pharmacological evaluation, especially for antidiabetic potential.